Biolearning Project: from and in the spiral of life - Castro Flores, Kattia Isabel (2023)
The following article shares the experience of the Biolearning project - learning from life, a training process of an inter-institutional initiative between the Ecumenical School of Religious Sciences of National University and the National Children’s Board (PANI), Costa Rica. Concepts such as self-care, collective care and revitalization are woven around this process. The main lines of the experience that will be shared, recover the learning obtained in these years (2015-2022). Finally, we want to record the challenges that are glimpsed in the future.